Entrepreneurship education for sustainable development: A designdriven approach - Roopsuwankun, Pattama; Woraphiphat, Issariya (Kasetsart Journal of Social Sciences, 2024)
Entrepreneurs for sustainable development are needed to achieve SDGs. However, there is a lack of professional training that enables learners to become sustainable entrepreneurs. This study proposes the integration of Education for Sustainable Development (ESD) with Design-Driven Entrepreneurship Education (DDEE), which could influence sustainable entrepreneurial intentions. Two hundred and seventy-seven vocational college students completed the online questionnaire. The results show that course design, teachers’ competencies, and peer interactions influence students’ sustainable entrepreneurial intention through the perceived benefits of learning. Additionally, students’ environmental consciousness impacts their sustainable entrepreneurial intentions. This study extends the theoretical contribution by connecting the sustainability and entrepreneurship constructs. It also provides a practical framework for Teachers of Education for Sustainable Development (TESD) to influence students to become sustainable entrepreneurs.